1995
DOI: 10.1177/000348949510400807
|View full text |Cite
|
Sign up to set email alerts
|

Myringosclerosis Caused by Increased Oxygen Concentration in Traumatized Tympanic Membranes Experimental Study

Abstract: The purpose of this study was to elucidate possible relationships between the oxygen concentration of the middle ear cavity and the development of myringosclerosis. Three groups of rats with myringotomized tympanic membranes were exposed to different oxygen concentrations of 10%, 15%, and 40%, respectively, for 1 week. A fourth group was kept in ambient air. Two other groups of rats with myringotomized and intubated tympanic membranes were exposed to oxygen concentrations of 10% and 40%, respectively, for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
98
3
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(106 citation statements)
references
References 13 publications
3
98
3
2
Order By: Relevance
“…TS affects the connective tissue layer and is characterised by an increase in collagenous fibres and hyaline degeneration. Many factors involved in wound healing may play a role in this pathological process [1][2][3][4] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…TS affects the connective tissue layer and is characterised by an increase in collagenous fibres and hyaline degeneration. Many factors involved in wound healing may play a role in this pathological process [1][2][3][4] .…”
Section: Discussionmentioning
confidence: 99%
“…One of them suggests that oxygen-derived free radicals may be an aetiological factor in the development of TS [3,5] . However, Atmaca et al [28] demonstrated that exogenous nitric oxide application did not alter the occurrence of TS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MS or TS frequently follows a myringotomy, ventilation tube insertion, recurrent otitis media, physical trauma, and middle ear infections. In addition, a genetic predisposition, immunological sensitivity, and local metabolic changes are factors that predispose a person to the development of TS [3][4][5] . Although the etiopathogenesis of MS is not fully understood, recent studies have reported that reactive oxygen samples (ROS), mechanical injury, and inflammatory diseases are the main factors in the development of MS, and antioxidant agents, free radical connective substances, and anti-inflammatory agents are effective in preventing MS [4,6] .…”
Section: Introductionmentioning
confidence: 99%